Non-cognitive ability and relative poverty in farmer households: an empirical study from rural China - Sun, Bochi; Yin, Han (Frontiers in Psychology, 2025)
Exploring the cognitive aspects of pro-social behavior is crucial for improving social well-being and strengthening social identity. Specifically, in today’s post-poverty alleviation era, it is vital to pay attention to how non-cognitive ability can alleviate the relative poverty of farmers and further promote the consolidation and expansion of poverty alleviation achievements from the perspective of pro-social behavior. This study incorporates non-cognitive abilities into a traditional economic model, constructing a theoretical framework to analyze their impact on the economic decision-making of farmer households. Utilizing rural sample data from the 2018 China Family Panel Studies, we employed the instrumental variable and two-stage least squares methods to empirically examine this effect. The main findings of the study are as follows. (1) The empirical test results of Hypothesis 1 indicate that an enhancement in non-cognitive abilities significantly reduces relative poverty, particularly traits such as conscientiousness and extraversion, whereas agreeableness, openness, and emotional stability show no significant impact. Notably, non-cognitive abilities have a more pronounced effect on female-headed and low-educated farmer households in Western China, thereby demonstrating inclusiveness. (2) The empirical test results of Hypothesis 2 indicate that improved non-cognitive abilities enhance the quality of economic decision-making by alleviating constraints, adjusting preferences, and enhancing expectations, thereby reducing relative poverty. To effectively mitigate relative poverty among farmer households, governments must promote and provide training for these non-cognitive abilities, thus bolstering self-development capabilities and improving economic decision-making.